Clinical characteristics and factors associated with mortality in idiopathic pulmonary fibrosis: An experience from a tertiary care center in Pakistan. (22nd May 2017) - Zubairi, Ali Bin Sarwar; Ahmad, Huzaifa; Hassan, Maryam; Sarwar, Sajjad; Abbas, Aamir; Shahzad, Talha; Irfan, Muhammad
Abstract: Introduction: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive interstitial lung disease (ILD) that predominantly affects older adults. IPF has the highest mortality burden of all ILDs. Data on mortality in patients with IPF is limited in developing countries. Objectives: To identify factors associated with mortality in patients with IPF at a tertiary care center in Pakistan. Methods: A retrospective chart review was conducted at the Aga Khan University Hospital (AKUH) in Karachi, Pakistan from January 2005 to December 2015. Patients were assessed for smoking status, clinical onset of disease, pulmonary hypertension, disease severity based on spirometry and hypoxemia. Results: A total of 239 cases were reviewed, of which 103 were non‐survivors. A total of 45 (18%) were current smokers and 71 (29.7%) were ex‐smokers. Smoking was more common in non‐survivors (56.3% P  ≤ .01). Pulmonary hypertension was present in 18.8% of patients. 95.4% of patients who had received pirfenidone treatment were alive at the time of study. On multivariate analysis, pirfenidone treatment (OR 0.03; 95% CI 0.01‐0.08), current smoking (OR 2.60; 95% CI 1.04‐6.58), age older than 60 years (OR 2.63; 95% CI 1.04‐6.58) and hypoxemia (OR 3.29; 95% CI 1.58‐6.84) were the factors associated with mortality. Conclusion: Smoking, age greater than 60 years and hypoxemia were identified as factors that increased the odds of mortality in IPF patients, whereas pirfenidone was found to lower the odds of mortality.